# |
ODE |
Mathematica |
Maple |
\[
{}y^{2} = x \left (y-x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y+y^{3}-x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 a x +b y+\left (2 c y+b x +e \right ) y^{\prime } = g
\] |
✓ |
✓ |
|
\[
{}\sec \left (x \right )^{2} \tan \left (y\right ) y^{\prime }+\sec \left (y\right )^{2} \tan \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = m y
\] |
✓ |
✓ |
|
\[
{}\frac {2 x}{y^{3}}+\left (\frac {1}{y^{2}}-\frac {3 x^{2}}{y^{4}}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (T+\frac {1}{\sqrt {t^{2}-T^{2}}}\right ) T^{\prime } = \frac {T}{t \sqrt {t^{2}-T^{2}}}-t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = \frac {\sin \left (x \right )}{y^{3}}
\] |
✓ |
✓ |
|
\[
{}p^{\prime } = \frac {p+a \,t^{3}-2 p t^{2}}{t \left (-t^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}\left (T \ln \left (t \right )-1\right ) T = t T^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = \frac {\sin \left (2 x \right )}{2}
\] |
✓ |
✓ |
|
\[
{}y-\cos \left (x \right ) y^{\prime } = y^{2} \cos \left (x \right ) \left (1-\sin \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-y+2 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 {y^{\prime }}^{3}+{y^{\prime }}^{2}-y = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{z -y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+T} = T^{\prime }
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \left (x^{2}-1\right ) = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x +y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\sec \left (\theta \right )^{2} = \frac {m s^{\prime }}{k}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (y^{2} a +b \right )
\] |
✓ |
✓ |
|
\[
{}n^{\prime } = \left (n^{2}+1\right ) x
\] |
✓ |
✓ |
|
\[
{}v^{\prime }+\frac {2 v}{u} = 3 v
\] |
✓ |
✓ |
|
\[
{}\sqrt {-u^{2}+1}\, v^{\prime } = 2 u \sqrt {1-v^{2}}
\] |
✓ |
✓ |
|
\[
{}\sqrt {1+v^{\prime }} = \frac {{\mathrm e}^{u}}{2}
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{x} = y \sin \left (x^{2}-1\right )-\frac {2 y}{\sqrt {x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+\frac {2 y}{x -y}
\] |
✓ |
✓ |
|
\[
{}v^{\prime }+2 u v = 2 u
\] |
✓ |
✓ |
|
\[
{}1+v^{2}+\left (u^{2}+1\right ) v v^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}u \ln \left (u \right ) v^{\prime }+\sin \left (v\right )^{2} = 1
\] |
✓ |
✓ |
|
\[
{}4 y {y^{\prime }}^{3}-2 x^{2} {y^{\prime }}^{2}+4 x y y^{\prime }+x^{3} = 16 y^{2}
\] |
✓ |
✗ |
|
\[
{}5 x^{\prime }+x = \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+y^{\prime }-{y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y-2 x y^{\prime }-y {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {x y}{x^{2}+1} = \frac {1}{x \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = -x^{2}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = \csc \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -y
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+x^{2} y = x^{3}-x^{2} \arctan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {x y}{x^{2}+1} = \frac {1}{x \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}x \left (-x^{2}+1\right ) y^{\prime }+\left (x^{2}-1\right ) y = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = \frac {\sin \left (2 x \right )}{2}
\] |
✓ |
✓ |
|
\[
{}x \left (-x^{2}+1\right ) y^{\prime }+\left (2 x^{2}-1\right ) y = a \,x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \sin \left (x \right ) = y^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }-x y = a x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = y^{n} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime } y^{2}+y^{3} = x -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \tan \left (x \right ) = y^{4} \sec \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y \sqrt {x^{2}-1}+x \sqrt {y^{2}-1}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{y}+1\right ) \cos \left (x \right )+{\mathrm e}^{y} \sin \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {2 a y-y^{2}}\, \csc \left (x \right )+y \tan \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (3+y\right ) y^{\prime } = x \left (3+2 y\right )
\] |
✓ |
✓ |
|
\[
{}x^{3}-3 x^{2} y+5 x y^{2}-7 y^{3}+\left (y^{4}+2 y^{2}-x^{3}+5 x^{2} y-21 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+4 x y+y^{2}+\left (2 x^{2}+2 x y+4 y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \cos \left (y\right )+\cos \left (x \right ) \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+\ln \left (y\right )+\frac {x y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -2 y\right ) y^{\prime }+2 y^{2}+x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}5 x y y^{\prime }-x^{2}-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+3 x y-y^{2}\right ) y^{\prime }-3 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+2 x y\right ) y^{\prime }-3 x^{2}+2 x y-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}5 x y y^{\prime }-4 x^{2}-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-2 x y\right ) y^{\prime }+x^{2}-3 x y+2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime }+2 x^{2}-3 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (3 x +2 y-7\right ) y^{\prime } = 2 x -3 y+6
\] |
✓ |
✓ |
|
\[
{}\left (6 x -5 y+4\right ) y^{\prime } = 2 x -y+1
\] |
✓ |
✓ |
|
\[
{}\left (5 x -2 y+7\right ) y^{\prime } = x -3 y+2
\] |
✓ |
✓ |
|
\[
{}\left (x -3 y+4\right ) y^{\prime } = 5 x -7 y
\] |
✓ |
✓ |
|
\[
{}\left (x -3 y+4\right ) y^{\prime } = 2 x -6 y+7
\] |
✓ |
✓ |
|
\[
{}\left (5 x -2 y+7\right ) y^{\prime } = 10 x -4 y+6
\] |
✓ |
✓ |
|
\[
{}\left (2 x -2 y+5\right ) y^{\prime } = x -y+3
\] |
✓ |
✓ |
|
\[
{}\left (6 x -4 y+1\right ) y^{\prime } = 3 x -2 y+1
\] |
✓ |
✓ |
|
\[
{}x = y+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime }-1-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\sqrt {\frac {1-y^{2}}{-x^{2}+1}} = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = a \left (y^{2}+y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}3 \,{\mathrm e}^{x} \tan \left (y\right )+\left (1-{\mathrm e}^{x}\right ) \sec \left (y\right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (x y+x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y-\left (y^{3}+x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (4 y+3 x \right ) y^{\prime }+y-2 x = 0
\] |
✓ |
✓ |
|
\[
{}3 y-7 x +7+\left (7 y-3 x +3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y-3 x +3\right ) y^{\prime } = 2 y-x -4
\] |
✓ |
✓ |
|
\[
{}x^{2}-4 x y-2 y^{2}+\left (y^{2}-4 x y-2 x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime }+\frac {x y^{\prime }-y}{x^{2}+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}a^{2}-2 x y-y^{2}-\left (x +y\right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 a x +b y+g +\left (2 c y+b x +e \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x^{2} y+4 x^{3}-12 x y^{2}+3 y^{2}-x \,{\mathrm e}^{y}+{\mathrm e}^{2 x}\right ) y^{\prime }+12 x^{2} y+2 x y^{2}+4 x^{3}-4 y^{3}+2 y \,{\mathrm e}^{2 x}-{\mathrm e}^{y} = 0
\] |
✓ |
✓ |
|
\[
{}y-x y^{\prime }+\ln \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y+1\right ) y-\left (1-x y\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}a \left (x y^{\prime }+2 y\right ) = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{4} {\mathrm e}^{x}-2 m x y^{2}+2 m \,x^{2} y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (2 x y+{\mathrm e}^{x}\right )-{\mathrm e}^{x} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y-2 x y^{2}-\left (x^{3}-3 x^{2} y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (x y+2 x^{2} y^{2}\right )+x \left (x y-x^{2} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}+2 x +2 y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}-x^{2} y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{4}+2 x y+\left (2 x^{3} y^{3}-x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|